2005
DOI: 10.1097/01.ju.0000146574.52402.d5
|View full text |Cite
|
Sign up to set email alerts
|

QUALITY IMPROVEMENT IN LAPAROSCOPIC RADICAL PROSTATECTOMY FOR pT2 PROSTATE CANCER: IMPACT OF VIDEO DOCUMENTATION REVIEW ON POSITIVE SURGICAL MARGIN

Abstract: Quality assurance efforts through pathological and intraoperative documentation review can help decrease the positive margin rate, particularly in organ confined disease. However, eradicating positive margins at the distal prostatic apex remains a challenge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 14 publications
2
28
0
1
Order By: Relevance
“…Finally, we find of benefit the continuous quality assurance and improvement program, by which pathologic and intraoperative documentation of positive surgical margins are reviewed with the purpose of understanding the factors leading to a surgical margin. This leads to a focus on improving surgical results, particularly in an environment where the standard set by the open radical prostatectomists is high [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we find of benefit the continuous quality assurance and improvement program, by which pathologic and intraoperative documentation of positive surgical margins are reviewed with the purpose of understanding the factors leading to a surgical margin. This leads to a focus on improving surgical results, particularly in an environment where the standard set by the open radical prostatectomists is high [20].…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, correlation between the results of the whole mount sections of the surgical specimen and the intraoperative findings seen on the video was studied to help understand the mechanism by which a positive surgical margin occurs and to improve our intraoperative detection of the correct plane of dissection in a given patient [20].…”
Section: Quality Improvementmentioning
confidence: 99%
“…Several papers have emphasized the importance of surgical margins in LRP and have shown how to reduce positive margin rates. [30][31][32][33] Touijer et al reported that a weekly case review conference involving surgeons, radiologists and uropathologists improved positive margin rates from 17.3% to 7.5%. 33 In another paper, Touijer et al reported that analysis of intraoperative video recordings correlating with pathological findings was helpful to understand the characteristics of positive surgical margins.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, in 1997, Schuessler et al described the first LRP reporting the feasibility of technique despite its association with long operative times [6]. Since that time, numerous European and US centers continued to improve and refine technical aspects of the laparoscopic approach [7,8].…”
Section: Introductionmentioning
confidence: 99%